Kelayakan Tes Diagnostik Four-Tier Multiple Choice untuk Identifikasi Konsepsi pada Materi Kesetimbangan Kimia - Nareswari Rachmadhaniar, Reta; Novita, Dian (Chemistry Education Practice, 2024)
The purpose of this study was to obtain the feasibility of a four-tier multiple choice (4TMC) diagnostic test instrument for the identification of conceptions on chemical equilibrium material in terms of validity, practicality, and effectiveness criteria. This type of research is ADDIE development research with the Analyze, Design, Development, and Evaluation stages. Validity is obtained from a validation sheet consisting of construct, content, and language validity which gets mode = 4, so that the four-tier multiple choice instrument is said to be valid. Practicality is obtained from a learner response questionnaire supported by a learner activity observation sheet. Practicality in terms of the student's response questionnaire is 84% with a very practical category, while the student activity observation sheet gets mode = 1, so the diagnostic test instrument is said to be practical. Effectiveness is obtained from the diagnostic test instrument reliability test. The Cronbach alpha value obtained in the reliability test was 0.798, so the diagnostic test instrument developed was declared reliable. Based on the results of validity, practicality, and effectiveness, the four-tier multiple choice diagnostic test instrument is declared suitable for use.